(untitled) (Research, Society and Development, 2021)
With the increasing global urbanization, city planning has become increasingly challenging and, consequently, the management of solid waste as well. Managing waste in an intelligent and innovative way is the solution. For this, several actors in society, such as green startups, also known as cleantechs, must act actively. In this perspective, the present study carried out a literature review on the relevant topics and conducted an applied, descriptive, qualitative research, using a case study method through an online questionnaire, with a company that was configured through perceived and underused opportunities in the industry of solid waste in Recife - PE, Brazil. Through the questionnaire, it was observed that the company can be considered a case of success, because, despite not yet having a strategic planning and a structured business model, in just one year the company grew its revenue by approximately 50%. With the resolution of the identified gaps, the company will be able to develop tangible future plans and possibly make partnerships with the government and expansion plans for other cities. Through this research, it was possible to verify that, in spite of being a little-explored business segment, there are several possibilities of performance, growth and profitability.